Development and in vitro characterization of floating sustained-release drug delivery systems of polyphenols. (April 2013) - Rosenzweig, Ohad; Lavy, Eran; Gati, Irith; Kohen, Ron; Friedman, Michael
Abstract The aim of this study was to develop and characterize floating stomach-retentive matrix tablets that will deliver polyphenols in a controlled release manner. The tablets were prepared by direct compression. A number of polymers were examined and egg albumin was chosen in light of a better performance in terms of floating behavior and decomposition time. Dissolution studies for three representative polyphenols loaded into a number of formulations were performed using the "f2" factor in order to compare release profiles of different polyphenols and formulations. The release data showed a good fit into the power law equation and zero-order kinetics has been determined for some of the systems. Erosion and textural analysis studies revealed that higher concentration of egg albumin results in a higher gel strength that is less susceptible to erosion, potentially leading to a prolonged delivery time of drug. The ability of egg albumin-based tablets to resist high mechanical forces was also determined, while comparison to cellulose-derived polymers revealed that the latter have a much lower ability to resist the same forces. The developed delivery system has the potential to increase the efficacy of the therapy for various pathological stomach conditions and to improve patient compliance.